Pengaruh Penggunaan Kombinasi Maltodekstrin De 5-10 dari Pati Beras (Oryza sativa) dengan Laktosa sebagai Pengisi Terhadap Kompresibilitas dan Komprimabilitas Tablet Ibuprofen - Syofyan, Syofyan; Rosanih, Rosanih; Arsyadi, Arsyadi (Fakultas Farmasi Universitas Andalas, 2011)
Has conducted research on the effect of the combined use of maltodextrin DE 5-10 of starch rice (Oryza sativa) with lactose as a filler to the compressibility and comprimability ibuprofen tablets. Mass properties of compressibility and comprimability examined and evaluated according to the quality of the tablet Indonesian pharmacopoeia. The results showed that the analysis using one-way ANOVA F calculation obtained 1,130 less than the value of 3.48 which means the F table did not show any difference between the formulas. It can be concluded that the difference in the levels of the combination of lactose-maltodextrin DE 5-10 of rice starch did not affect the value of compressibility and tablet dosage ibuprofen komprimabilitas.